Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Test: 14

Answer

$\dfrac{3}{x-1}$

Work Step by Step

$\dfrac{6}{x^2-1}+\dfrac{3}{x+1} = \dfrac{6}{(x+1)(x-1)}+\dfrac{3}{x+1} = \dfrac{6(x+1)+3(x+1)(x-1)}{(x+1)(x-1)(x+1)} = \dfrac{(x+1)[6+3(x-1)]}{(x+1)(x-1)(x+1)} = \dfrac{6+3(x-1)}{(x+1)(x-1)} = \dfrac{6+3x-3)}{(x+1)(x-1)} = \dfrac{3x+3}{(x+1)(x-1)} = \dfrac{3(x+1)}{(x+1)(x-1)} = \dfrac{3}{x-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.